Endoscopic treatment of large pancreatic fluid collections (PFC) using self-expanding metallic stents (SEMS) – a two-center experience - Chaves, Dalton Marques; Mönkemüller, Klaus; Carneiro, Fred; Medrado, Bruno; dos Santos, Marcos; Wodak, Stephanie; Reimão, Sílvia; Sakai, Paulo; de Moura, Eduardo (Endoscopy International Open, 2014)
Background/study aim: During the last several years, endoscopic ultrasound (EUS)-guided pancreatic fluid collections’ (PFC) drainage has evolved into the preferred drainage technique. Recently, self-expanding metallic stents (SEMS) have been used as an alternative to double pigtail stents, with the advantage of providing a larger diameter fistula, thereby decreasing the risk of early obstruction and also allowing for direct endoscopic exploration of the cavity. The aim of this study was to evaluate the technical and clinical success, safety, and outcome of patients undergoing EUS-guided drainage of complex PFC using SEMS.Patients/materials and methods: The study was conducted at two tertiary hospitals from January 2010 to January 2013. All patients with PFC referred for endoscopic drainage were enrolled in a prospective database. The inclusion criteria were: (1) patients with pseudocysts or walled-off necrosis based on the revised Atlanta classification; (2) symptomatic patients with thick PFC; (3) PFC that persisted more than 6 weeks; and (4) large PFC diameter (≥ 9 cm). The exclusion criteria consisted of coagulation disorders, PFC bleeding or infection, and failure-to-inform written consent.Results: A total of 16 patients (9 females, 7 males; mean age 52.6, range 20 – 82) underwent EUS drainage with SEMS. There were 14 cases of pseudocysts and 2 cases of walled-off necrosis. The etiologies of the PFC were mainly gallstones (8 of 16 patients, 50 %) and alcohol (5 of 16 patients, 31 %). Technical success was achieved in 100 % of the cases. All patients had a complete resolution of the PFC.Conclusion: Transmural EUS-guided drainage of complex PFC using SEMS is feasible, appears safe, and is efficacious. However, the exchange of the UC (uncovered)-SEMS for plastic stents is mandatory within 1 week. Future prospective studies, preferably multicenter studies, comparing SEMS versus traditional plastic stents for the drainage of PFC are warranted.